Killing Guiltlessly as Reaction of Sadistic Personality Disorder in Euripides’ Medea (A Psychological Approach in Literature) - Hadiyanto Hadiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
ABSTRACT  This research paper is aimed at analyzing one of Euripides’ well-renowned classical literary works entitled Medea by focussing on Medea as the main character of the story, Medea’s psychological state, psychological reason, and sadistic personality disorder reaction. This research paper uses psychological approach in analyzing the related psychological phenomena in Euripides’ Medea. The resut of the research indicates that Medea, who gets accustomed to being raised in a barbarous family and living in a barbaric environment, has a natural impulsive behaviour to kill other persons guiltlessly. Key words: killing, guiltless feeling, sadistic personality disorder